A School in a Paediatric Oncology Unit: The Crucial Role of Education in the Context of a Serious Illness - Fierros-Sánchez-Cuenca, Marta (2020)
The Montepríncipe School works in the education of children and teenagers diagnosed with cancer, supporting the continuity of their academic and social scholarship. School attendance permits them to continue with their previous lives, which is an indication of integration and normalization of disease. The school relies on a multidisciplinary team, which includes teachers, psychologists, music therapists, and volunteers working, all together,With the Unit health professionals. This article describes the performance of the Hospital School and the way it permits to integrate and normalize disease in the lives of children. In order to do so, we accomplished an experimental, quantitative, longitudinal study considering daily school attendance of 36 students, as an average, over five school years (2012-2017). The attendance turned out to be 90%, though it was non-compulsory, and it maintained stable through the years. Additionally, we measured academic performance to verify that school attendance was effective. The sample was formed by 14 students, whose Spanish Language and Mathematics marks were compared before and after treatment. The outcomes showed an improvement of one point in each subject in average, which demonstrates that daily attendance to the Hospital School contributes to integrate disease into the lives of the children and, even, to improve their academic results.